InPNBi/InP heterostructures for optoelectronic applications: A k‧p investigation. (October 2022) - Mal, Indranil; Samajdar, D.P.
Abstract: We have thoroughly investigated various potential possibilities of exploiting InPNBi for electronic and optical applications considering the 16-band k∙p perturbation Hamiltonian. Taking into account strain-relaxed condition for InPNBi with InP by maintaining a specific ratio (0.92) between N and Bi, we have figured out the electronic bandgap as 0.782 eV, equivalent wavelength of ∼1.58 μm, and spin–orbit coupling energy (ΔSO ) as 0.173 eV of InP0.904 N0.046 Bi0.05 respectively. An extensive range of electronic bandgaps and corresponding operating wavelengths spanning from 1.42 eV (∼0.9 μm) to 0.401 eV (∼3 μm) are observed for N and Bi impurity concentrations up to 10% and 9.2%, respectively. Incorporation of both Bi and N impurity consequences to reduction in electron effective mass of InPNBi (0.065 m0 ) by ∼1.2 times with respect to the host InP (0.079m0 ), which boosts the optical properties of InPNBi/InP quantum confined heterostructures. Increasing impurity concentration and the applied electric field leads to red shift in the gain spectra and reduction in peak amplitude, which facilitates the likelihood of realizing InPNBi/InP for the optical modulators, 1 eV solar cells, and infrared detectors.